A semiotic analysis on female representation in music videos and their readings by young female viewers - Abella, Patricia A.
"This is a semiotic study in the favorite music videos of young female viewers in Lucena City. It also includes a comparison of the readings of the researcher with the readings of the young female viewers. A survey was made among students in eight (8) schools in Lucena City on their three top favorite music videos. The results were "This I Promise You" by N\Sync, "My Love" by Westlife, and "Shape of My Heart" by The Backstreet Boys. Based on these results, the researcher analyzed these videos using the semiotic approach. Each video was analyzed denotatively and connotatively. The denotative meanings were then broken down into signifiers and signifieds. The connotative meanings were broken down into the use of paradigms and syntagms. Following the survey was a focus group discussion (FGD) among six (6) respondents, taken from the population used in the previous survey. The respondents recalled and always mentioned one video which was not included in the top three videos in the survey. It was entitled "Stan", performed by Eminem. Because of this, the researcher decided to include this in her analysis. The researcher applied the semiotic approach and Del Rosario's The Patriarchal Image Propagation Model in this study. The researcher found concepts and indicators which she considered an oppression to women. These concepts were projected by the shots, storyline, lyrics and characters that the video contains. There were female representations recognized by the researcher which was not recognized by the respondents. Certain representations were analyzed and understood differently by the respondents and the researcher."